'Frustrated' hydrogen bond mediated amphiphile self-assembly – a solid state study. Issue 37 (1st September 2016) - Blackholly, Laura R.; Shepherd, Helena J.; Hiscock, Jennifer R.
Abstract : The effects of hydrogen bond donor acidity and counter cation within a 'frustrated' self-assembled, hydrogen bonded system. Abstract : Herein, we present the synthesis of ten structurally related 'frustrated' amphiphiles, from which were obtained eleven single crystal X-ray structures, allowing observation of the hydrogen bonding modes present in the solid state. We previously reported the synthesis of a novel amphiphilic salt which contains both hydrogen bond donating (HBD) and hydrogen bond accepting (HBA) functionalities. This amphiphilic salt was shown to self-associate in the solution state, aided by the formation of hydrogen bonds. The exact nature of the hydrogen bonding modes involved in this self-association process remains unclear due to the combination of HBD and HBA groups present in the amphiphile structure. This results in a 'frustrated' system with access to a variety of possible hydrogen bonding modes.